Dosimetric impact of bolus thickness and immobilization mask use in postmastectomy radiotherapy: a chest wall thickness–based analysis - Shang, Qing-Jun; Zhang, Meng; Zhao, Bing-Xin; Wang, Qi; Gao, Wen; Zhang, Bi-Yuan; Wang, Hai-Ji; Guo, Tian-Hui (Frontiers in Oncology, 2026)
PurposePostmastectomy radiotherapy (PMRT) requires a balance between optimal target coverage and organ-at-risk (OAR) sparing. Thermoplastic masks and different bolus thicknesses are frequently applied in clinical practice, yet their combined dosimetric effects and dependence on chest wall thickness remain insufficiently defined.Methods and materialsSeventeen breast cancer patients treated with PMRT were retrospectively analyzed. For each patient, six intensity-modulated radiotherapy (IMRT) plans were generated, combining the presence or absence of a thermoplastic mask with bolus thicknesses of 0, 3, and 5 mm. Dosimetric parameters of the skin, planning target volume (PTV), OARs, and treatment efficiency (monitor units, MU) were compared across plans. Subgroup analyses were performed according to chest wall thickness (<4.1 cm, 4.1–5.0 cm, >5.0 cm). Correlations between chest wall thickness and dosimetric indices were evaluated using Spearman’s rank analysis.ResultsApplication of bolus improved dose homogeneity and PTV coverage, reduced lung dose and MU, but increased skin dose. The thermoplastic mask alone raised skin dose, functioning as an unintended compensator. In patients without masks, bolus effects on skin and OARs were more pronounced, suggesting greater sensitivity to compensation thickness. Chest wall thickness demonstrated negative correlations with skin dose, lung exposure, and MU. Patients with thin chest walls (<4.1 cm) derived the greatest benefit from bolus application, whereas patients with thick chest walls (>5.0 cm) showed minimal dosimetric improvement.ConclusionsBoth thermoplastic masks and bolus significantly affect PMRT dosimetry. Bolus provides improved PTV coverage and lung sparing at the cost of higher skin dose, while thermoplastic masks act as unintended compensators. Chest wall thickness strongly influences these effects, supporting individualized selection of bolus and mask use, particularly for patients with thinner chest walls.